The Effect of Application Usability, Service Quality, and E-Satisfaction on Influencing Purchase Intention of GO-FOOD Customers - Wiria Chandra; Alexander Wirapraja (Program Studi Sistem Informasi Universitas Atma Jaya Yogyakarta, 2020)
Changing the habits of modern society and the influence of social media into a big opportunity for the small food and beverage industry, by marketing products through Go-Food, the seller in the sense of restaurants or micro-businesses can reach consumers more broadly, this research wants to know the factors that influence perceptions consumers in shaping buying interest by testing the purchase intention factor with the variable usability application, service quality and e-satisfaction, testing is conducted on 130 respondents with a sampling technique using purposive sampling and using the equation modelling (SEM) measurement method and the results are obtained that the purchase intention factor influenced by the ease of use, level of service and electronic satisfaction felt by consumers.